2017
DOI: 10.4172/2167-0870.1000319
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Agglomerative Cluster Analysis as a Trial Method Revealing Developmental Coordination Disorder (DCD) Subtypes

Abstract: Background: There is increasing evidence that children with DCD have been classified into distinguishable 'subtypes' mainly based on perceptual-motor, fine and gross motor skills. Previous research efforts define and describe in detail subgroups of DCD using the methods of cluster analysis. The hierarchical agglomerative cluster analysis seems to be an effective statistical method to identify homogeneous subtypes in the developmental disorder literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…More specifically, Lust et al (2022) identified four major subtypes (all reduced motor skills, reduced motor skills except for gross motor skills, gross motor/balance difficulties, fine motor difficulties), while Vaivre-Douret et al (2011) found three subtypes (ideomotor dyspraxia, visual spatial and visual constructional dyspraxia, mix dyspraxia). When considering additional cognitive symptoms, Asonitou et al (2022) identified six clusters based on motor and cognitive assessment among students with and without DCD. Therefore, it is likely there is substantial complexity in the motor symptoms of DCD and the related motor system, which only increases when considering cognitive interactions.…”
Section: Complexity Of Motor and Cognitive Symptoms Of Dcdmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, Lust et al (2022) identified four major subtypes (all reduced motor skills, reduced motor skills except for gross motor skills, gross motor/balance difficulties, fine motor difficulties), while Vaivre-Douret et al (2011) found three subtypes (ideomotor dyspraxia, visual spatial and visual constructional dyspraxia, mix dyspraxia). When considering additional cognitive symptoms, Asonitou et al (2022) identified six clusters based on motor and cognitive assessment among students with and without DCD. Therefore, it is likely there is substantial complexity in the motor symptoms of DCD and the related motor system, which only increases when considering cognitive interactions.…”
Section: Complexity Of Motor and Cognitive Symptoms Of Dcdmentioning
confidence: 99%
“…While there is no doubt DCD involves substantial motor learning and execution difficulties, there are still aspects of the motor symptoms which are not yet fully understood. This is evident through a lack of consensus on the potential for and nature of DCD subtypes (Vaivre-Douret et al, 2011;Lust et al, 2022), which becomes even more complex when considering additional subtypes for motor and cognitive skills (Asonitou et al, 2022). Furthermore, the motor system does not act alone, often integrating cognitive resources such as executive functions Meachon 10.3389/fnhum.2022.1082209 (Diamond, 2000;Asonitou et al, 2012;Leisman et al, 2016;Möhring et al, 2020).…”
Section: Complexity In Primary and Secondary Symptoms Of Dcdmentioning
confidence: 99%